Analisa Akibat Hukum Wanprestasi dalam Perjanjian Sewa Menyewa Tanah dan Bangunan - Angeline Angeline; Ariawan Gunadi (Syntax Corporation, 2023)
Leasing is an agreement between a party and another party who binds himself to give the other party the enjoyment of an item for a certain time with payment according to the price the party can afford to pay. In this case, the parties to the lease agreement also have rights and obligations, as for what is the right of the renting party is to receive a predetermined rental price. While in Article 1550 paragraph (1) of the Civil Code, the obligation for the renting party in the lease agreement is to deliver the leased goods to the tenant. The lessee is entitled to pand beslag, which is a confiscation carried out by the court at the request of the lessee such as land and buildings that stand on it in the event that the lessee is in arrears with the rent and does not pay in full the rent arrears. A lessee also has the right to request the cancellation of the agreement by providing compensation if the lessee commits an act of default or breaks the agreement before the end of the agreement.